Educational Management in Character Formation Through the Role of the Family and the Exemplary Behavior of Pesantren Caregivers - Novi Andriani; Abidin, Muh. Mukhlis; Sa’diyah, Maidatus; Al Kahfi, Sidik; Hidayat, Mangsur (Tebuireng: Journal of Islamic Studies and Society, 2025)
Based on the results of the study shows that the importance of building the character of students today, because character education will affect the lives of students in the future. The character building of students is strongly influenced by families and caregivers at Pesantren Roudlotut Thullab Magelang. In shaping the character of students, parents and caregivers work together to supervise the growth and development of children when at home and when in pesantrens. In character building at Pesantren Roudlotut Thullab Magelang, caregivers and all staff carry out a continuous teaching and learning process both through lessons in formal and non-formal educational institutions.  In addition, to shape the character of students is also done by making rules that must not be violated and if one commits a violation, students are subject to punishment, this is done so that students get used to being disciplined and responsible students. Further character building is also carried out by motivating all students, one of which is motivation from families and caregivers of pesantrens. The key to the success of education management in character building through the role of family and the example of caregivers at Pesantren Roudlotut Thullab Magelang is that both have paid attention to POAC (planning, organizing, actuating, controlling).